Holistic and Transdisciplinary Character of Contemporary Academic Education - Żłobicki, Wiktor (Instytut Pedagogiki Uniwersytetu Wrocławskiego, 2019)
Nowadays, in academic education, we are becoming more and more aware of the crisis of scientific knowledge, knowledge which does not answer the global problems resulting from the increasing complexity of the world. This situation confronts scientists with the challenge of not only looking for comprehensive knowledge, but also crossing and moving disciplinary boundaries. It seems that the structure of knowledge disciplines, which has its roots in the nineteenth century – as well as the boundaries set between them, constitute a barrier to the development of knowledge. It is worth showing more flexibility in the division of disciplines and flexibility about their boundaries and turn to holism and transdisciplinarity in science.
Keywords: holism; disciplinarity; knowledge; science; development; borders; education